Misinformation Drives Low Human Papillomavirus Vaccination Coverage in South African Girls Attending Private Schools - Milondzo, Tracy; Meyer, Johanna C.; Dochez, Carine; Burnett, Rosemary J. (Frontiers in Public Health, 2021)
Background: Cervical cancer, caused by persistent human papillomavirus (HPV) infection, is the leading cause of female cancer deaths in South Africa. In 2014, the South African National Department of Health introduced a free public sector school-based HPV vaccination programme, targeting grade 4 girls aged ≥9 years. However, private sector school girls receive HPV vaccination through their healthcare providers at cost. This study investigated HPV vaccination knowledge, attitudes and practices of caregivers of girls aged ≥9 years in grades 4–7 attending South African private schools. Methods: A link to an online survey was circulated to caregivers via an email sent to school principals of all private schools in four provinces enrolling girls in grades 4–7. Following a poor post-reminder response, a paid Facebook survey-linked advert targeting South African Facebook users aged ≥25 years nationally was run for 4 days, and placed on the South African Vaccination and Immunisation Centre's Facebook page for 20 days. Results: Of 615 respondents, 413 provided HPV vaccination data and 455 completed the knowledge and attitudes tests. Most (76.5%) caregivers had good knowledge and 45.3% had positive attitudes. Of their daughters, 19.4% had received ≥1 dose of HPV vaccine. Of caregivers of unvaccinated girls, 44.3% and 41.1%, respectively were willing to vaccinate their daughters if vaccination was offered free and at their school. Caregivers of unvaccinated girls were more likely [odds ratio (OR): 3.8] to have been influenced by “other” influences (mainly online articles and anecdotal vaccine injury reports). Of caregivers influenced by their healthcare providers, caregivers of unvaccinated girls were more likely (OR: 0.2) to be influenced by alternative medical practitioners. Caregivers of vaccinated girls were more likely to have good knowledge (OR: 3.6) and positive attitudes (OR: 5.2). Having good knowledge strongly predicted (OR: 2.8) positive attitudes. Having negative attitudes strongly predicted (OR: 0.2) girls being unvaccinated. Conclusion: Providing free school-based HPV vaccination in the private sector may not increase HPV vaccination coverage to an optimal level. Since misinformation was the main driver of negative attitudes resulting in <20% of girls being vaccinated, an advocacy campaign targeting all stakeholders is urgently needed.